2018
DOI: 10.4103/jcd.jcd_240_17
|View full text |Cite
|
Sign up to set email alerts
|

Rotary science and its impact on instrument separation: A focused review

Abstract: Efficient endodontic treatment demands thorough debridement of the root canal system with minimal procedural errors. The inherent weakness of nickel–titanium alloys is their unexpected breakage. Modifications in the design, manufacturing, thermomechanical and surface treatment of alloys and advancements in movement kinetics have shown to improve the fatigue properties of the alloys, reducing the incidence of separation. This review enlightens the impact of these factors on fatigue properties of the alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 98 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…These changes result in enhanced the file physical properties such as cutting efficacy has been increased and the fracture resistance also elevated. (26,27) However, sterilization in some studies has been showed that not necessarily effective on the cyclic fatigue of the files. (28) The choosing of two or four cycle sterilization cycles in this study based on reports showed that NiTi file can be used to shape up to 10 curved root canals.…”
Section: Discussionmentioning
confidence: 99%
“…These changes result in enhanced the file physical properties such as cutting efficacy has been increased and the fracture resistance also elevated. (26,27) However, sterilization in some studies has been showed that not necessarily effective on the cyclic fatigue of the files. (28) The choosing of two or four cycle sterilization cycles in this study based on reports showed that NiTi file can be used to shape up to 10 curved root canals.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent studies have shown that sodium hypochlorite can corrode metal and alloys used in the manufacturing of endodontic files which causes, selective removal of nickel from the surface of Ni-Ti instrument, leading to micro-pitting. 9 These surface alterations can be best analyzed using SEM and AFM evaluation. Since scanning electron microscopy cannot give a qualitative data on surface irregularities, AFM was the chosen method of surface roughness evaluation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we had the same result with significant patient satisfaction who got their treatment from post graduate compared to house officer. 24 As result shows that there is significant difference in post-operative pain after the treatment from house officers no matter what type of treatment is given so it is concluded that house officers required more training and skills as compared to the postgraduates. It is also recommended that frequent brain storming and skill polishing activities like journal clubs, presentations and interactive sessions should be arranged during house job or internship phase to make them a strong part of dental fraternity.…”
Section: Disscussionmentioning
confidence: 97%